LOCAL INJECTION OF PLATELET-RICH PLASMA VERSUS STEROID INJECTION IN PLANTAR FASCIITIS: A COMPARATIVE STUDY - Padmaraj Patil; Satish Patil; Amit Jagdale; pravin sonune (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objectives: The aim of the study was to compare the effect of local steroid injection and injection of platelet rich plasma in patients with plantar fasciitis. Methods: Eighty patients diagnosed to be having plantar fasciitis were included in this study on the basis of a predefined inclusion and exclusion criteria. The study was conducted in PIOS Medilinks Pvt limited jaysingpur Kolhapur India. The duration of study was 1 year from January 2022 to January 2023. Institutional ethical committee approved the study. Patients were assigned to two equal, parallel groups of 40 patients each. Patients in one group were given local steroid injection (Group S) whereas patient in other group was given local injection of platelet rich plasma (Group P). The patients were followed up for 12 weeks. Visual analog score (VAS) Score and American orthopedic foot and ankle society (AOFAS) score were compared at each follow-up visit. For statistical purposes, p<0.05 was taken as statistically significant. Results: The M: F ratio in Group P and Group S was found to be 1:1.85 and 1:1.50, respectively. Overall, most commonly affected age group was 41–50 years (32.50% and 37.50%) followed by 51–60 years (25% and 27.50%). The analysis of body mass index (BMI) in patients of Group S showed that among 40 patients 12 (36.67%) patients were obese (BMI ≥30) and 15 (30%) patients were overweight (BMI ≥25 but <30). In Group P, 22 (73.33%) patients were either obese or overweight (BMI ≥25). IN our study from time of presentation till 4 weeks the reduction in VAS score was found to be comparable in both the groups. However, at the time of 8-week and 12-week follow-up, mean VAS score in Group P was less as compared to group S and the difference was found to be statistically significant (p<0.05). At the time of follow-up at 12 weeks, better AOFAS score was seen in Group P (90.12±14.26) as compared to group S (82.08±8.68) and the difference was found to be statistically significant (p=0.0032). Conclusion: Injection of platelet rich plasma is found to have better outcomes as compared to steroid injection in plantar fasciitis treatment over the course of 12 weeks as assessed by improvement in VAS and AOFAS scores.